The Influence Of Teacher’s Performance On The Students’ Achievement - Destiani Rahmawati (STAI Asy-Syukriyyah, 2012)
Teacher’s performance is the way a teacher acts, does and performs the lesson during teaching learning process. Performance also consists of facial expression, gesture, body movement, vocal intonation and inflection. Teacher’s performance plays an important role in teaching and learning process because the way a teacher performs a lesson influences the students’ achievement. By showing good preparation and good performance, students will be interested in paying attention to the lesson given. In other words, the better performance a teacher has, the higher achievement students get. The purpose of this study is to know the correlation between teacher’s performance and student’s achievement. This study was conducted at English Department of Teacher Training and Education Faculty, STKIP KUSUMA NEGARA pokjar Gading Serpong. The data were obtained from 40 students by means of giving them questionnaires of teacher’s performance and students’ English achievement test. Both scores were analyzed by using Pearson Product Moment correlation. The result shows that the correlation between teacher’s performance and students’ achievement is r. 0.90. It means that there is a high correlation between teacher’s performance and students’ achievement.